Equity in Health Care: A Comparative Study Between the United Kingdom and the United States of America - Gardner, Stephanie (2011)
Aim - The aim of this study is to identify, compare and discuss the similarities and differences in the equity of healthcare service provision between universal and private healthcare systems, and determine whether universal healthcare systems have a positive impact upon the equity of service provision for service users. Background - The United Kingdom has a universal healthcare system in the National Health Service, and the United States of America is the only developed country to maintain a private healthcare system. Assumptions are held that attribute inequity of healthcare service provision to systems that do not utilise a universal healthcare coverage, however, these assumptions may well be unjustified. Methods - A comparative research approach was used to evaluate statistical data relating to cardiovascular diseases, vaccine-preventable diseases and maternal health. Methods used include the use of official organisational data on mortality, and uptake of vaccinations. Findings – There were differences in crude death rates for cardiovascular diseases and maternal causes. However, standardised death rates showed considerable differences between the countries and uptake of routine vaccinations was also unequal. Conclusion – The provision of universal care coverage will not necessarily have a positive impact upon equity in healthcare as personal barriers to access are highly reported amongst populations. Organisations must first address barriers to access in precedence to transition to more widespread services.